DO SILÊNCIO ÀS VOZES: BIBLIOTECA ESCOLAR SOB O PONTO DE VISTA DAS CRIANÇAS - NUNES, MARISTELA APARECIDA (2016)
Although at the beginning of the XXI century studies from several fields have provided a wider knowledge of child development, it is still not guaranteed to the child the right to have their interests and specific needs properly recognized. Furthermore, it is observed that in the school, the child, as well as the school library - key elements on the educational process - are also devaluated. However, childhood area studies supported by assumptions of Sociology and Childhood Anthropology (1990), point out to the need of looking at children with different eyes, considering them as producers of history and culture, thought in the construction of social relations. Similarly, the school library must be re-signified as a place to encourage reading, acquiring knowledge, culture, encouraging the taste for reading and the constitution of critical subjects. Given the above considerations, this research is justified by the necessary development of considering children's culture, listening and recognizing their interests, as well as the understanding of children as active subjects in educational practices - which we consider essential in schools and in social area - and the professional experience of the researcher as active educator in a school library. Thus, the current study aims at recognizing and discussing the perception of the library from the point of view of children. This larger goal has deployed in others: to present historical issues and the potential of the school library, create opportunities for children to expose their ideas about school library, to identify how the library space in the research institution is organized and which practices are developed there. This research was built by bibliographic and field studies. We looked into childhood area of Literature and the school library. Characterized by qualitative nature, we stand in the postulates of Ludke and Andre (1986) Fazenda (2008) and Triviños (2009). The methodological procedures were semi structured interview under the postulates of Manzini (2003) and Kaufmann (2013) and observation (in situ) of the library's physical space, and processing of the data sat on content analysis (Bardin, 2011 ). The study subjects were children, students in the early years of elementary school, and the data collection took place in the library of a municipal school in the city of Guarapuava/PR. In general, the conversations with the children showed us that they like to visit the library and would like to go more often to this space, the library is a place of silence, which requires immobility, and they have the desire to be able handle more books as with the home loan. This study enabled us to recognize that the child is often silenced in school and their participation is limited to sitting and being quiet. Also, we realized that the very existence or absence of the library in the school shows a conception of teaching, child and human development.